Commodity risk assessment of Cornus alba and Cornus sanguinea plants from the UK - EFSA Panel on Plant Health (PLH); Claude Bragard; Paula Baptista; Elisavet Chatzivassiliou; Francesco Di Serio; Paolo Gonthier; Josep Anton Jaques Miret; Annemarie Fejer Justesen; Alan MacLeod; Christer Sven Magnusson; Panagiotis Milonas; Juan A. Navas‐Cortes; et al. (EFSA Journal)
Abstract The European Commission requested the EFSA Panel on Plant Health to prepare and deliver risk assessments for commodities listed in Commission Implementing Regulation (EU) 2018/2019 as ‘high risk plants, plant products and other objects’. Taking into account the available scientific information, including the technical information provided by the applicant country, this Scientific Opinion covers the plant health risks posed by the following commodities: Cornus alba and Cornus sanguinea bare‐root plants and rooted plants in pots up to 7 years old imported into the EU from the UK. A list of pests potentially associated with the commodities was compiled. The relevance of any pest was assessed based on evidence following defined criteria. Four EU quarantine pests (Meloidogyne fallax, Phytophthora ramorum (non‐EU isolates), tobacco ringspot virus, and tomato ringspot virus) and one EU non‐regulated pest (Discula destructiva), were selected for further evaluation. For the selected pests, the risk mitigation measures implemented in the technical dossier from the UK were evaluated taking into account the possible limiting factors. For these pests, an expert judgement is given on the likelihood of pest freedom taking into consideration the risk mitigation measures acting on the pest, including uncertainties associated with the assessment. The degree of pest freedom varies among the pests evaluated, with P. ramorum being the pest most frequently expected on the imported C. alba and C. sanguinea plants. The Expert Knowledge Elicitation indicated, with 95% certainty, that between 9823 and 10,000 bare‐root C. alba and C. sanguinea plants per 10,000 will be free from P. ramorum.